A microbiological study of neonatal conjunctivitis in two hospitals in Tehran, Iran - Afjeiee, Seyed Abolfazl (Asian Pacific Tropical Medicine Press, 2013)
OBJECTIVE: To determine the prevalence of neonatal conjunctivitis and to identify the causative agents of ophthalmia neonatorum in two university affiliated hospitals from 2008 to 2009. METHODS: All neonates admitted in the neonatal department during the study period were examined for the presence of conjunctivitis. Two swab specimens containing epithelial cells of the conjunctiva were collected from newborns presenting with conjuntival inflammation. Laboratory diagnosis was based on direct smear for Gramstaining and bacterial culture. The isolated bacteria were identified using standard procedures. PCR and cell culture were used for identification. RESULTS: Of the 2 253 neonates, (age ranged 1–30 days), clinical findings of conjunctivitis were found in 241 cases (10.7%). The most commonly isolated bacteria were Coagulase negative staphylococci, (n=130, 53.9%); Chlamydia trachomatis was the second most common cause of acute neonatal conjunctivitis (n=40, 16.6%). Bacterial cultures were negative in 47 neonates (19.5%) despite clinical signs of conjunctivitis. The median age at presentation for bacterial culture positive was day 8 of life. CONCLUSIONS: Neonatal conjunctivitis is prevalent in newborns; Gram positive cocci and Chlamydia trachomatis are the most common causative organisms.